Effects of Crest Morphology on Lingual Concavity in Mandibular Molar Region: an Observational Study - Tansu Çimen; Neset Volkan Asar; Samir Goyushov; Onurcem Duruel; Tolga Fikret Tözüm (Stilus Optimus, 2023)
Objectives: The aim of this radiological study is to evaluate the lingual concavity dimensions and possible implant length in each posterior tooth region according to posterior crest type classification by using cone-beam computed tomography. Material and Methods: According to inclusion criteria, 836 molar teeth regions from 209 cone-beam computed tomography images were evaluated. Posterior crest type (concave, parallel, or convex), possible implant length, lingual concavity angle, width, and depth were recorded. Results: In each posterior tooth region, concave (U-type) crest was detected most frequently while convex (C-type) was the lowest. Possible implant length values were higher in second molar regions than first molars. Lingual concavity width and depth were decreasing from second molars to first molars for both sides. Additionally, lingual concavity angle showed higher values in second molar sites than first molars. In all molar teeth regions, lingual concavity width values were the highest in concave (U-type) crest type while they were the lowest in convex (C-type) crest type (P < 0.05). Lingual concavity angle values were recorded as the highest in concave (U-type) and the lowest in convex (C-type) crest type at the left first molar and right molars (P < 0.05). Conclusions: The lingual concavity dimensions and possible implant length may vary according to crest type and edentulous tooth region. Due to this effect, the surgeons should examine crest type clinically and radiologically. All parameters in the present study are decreasing while moving from anterior to posterior as well as from concave (U-type) to convex (C-type) morphologies.